QSAR Study Between LC50 of Linear Simple Conjugated Polyene Compounds in Fish and UV Maximum Wave Length by the Use of Randic Index - (ARMAN) TAHERPOUR, AVAT; TAHERPOUR, AREZOU; TAHERPOUR, OMID (Asian Journal of Chemistry, 2010)
In this study, the relationship is demonstrated between the Randic index and the calculated scales of LC50 in 96 h for fish by the use of EPI-suit v3.12 package, with maximum UV wavelength (λmax) for the linear simple conjugated polyenes. The interesting results of concerning among these calculated scales of LC50, λmax and the Randic index for this compounds are presented. It seems that these results can use in environmental and chemical laboratory of veterinary studies.